2010
DOI: 10.1016/j.jtcvs.2009.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of direct myocardial protective effect of atrial natriuretic peptide in cardiac surgery

Abstract: Ischemia-reperfusion injury was inhibited with equal effectiveness by atrial natriuretic peptide both during ischemia and immediately before reperfusion, acting directly on myocardium through cyclic guanosine monophosphate. Atrial natriuretic peptide may be useful as a supportive measure for patients with long aortic crossclamping time or difficulties in weaning from cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…[11][12][13][14][15][16] In an experiment study, cyclic guanosine monophosphate was increased by the administration of hANP, and myocardial protective effects were reported. 17,18) Recently, continuous intravenous administration of hANP or BNP have been performed in cardiac surgery worldwide, its cardiac and reno-protective effects have been reported. 19,20) The only large-scale studies of hANP performed so far are a multicenter study of hANP administration after reperfusion therapy in patients with acute myocardial infarction (J-WIND study).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] In an experiment study, cyclic guanosine monophosphate was increased by the administration of hANP, and myocardial protective effects were reported. 17,18) Recently, continuous intravenous administration of hANP or BNP have been performed in cardiac surgery worldwide, its cardiac and reno-protective effects have been reported. 19,20) The only large-scale studies of hANP performed so far are a multicenter study of hANP administration after reperfusion therapy in patients with acute myocardial infarction (J-WIND study).…”
Section: Discussionmentioning
confidence: 99%
“…Sezai, et al reported that carperitide acted to reverse these changes in every aspect. [13][14][15][16][17][18] They administered the drug at 0.02 µg/kg/min from the start of CPB, after taking into consideration that their patients did not have heart failure before surgery and might become dehydrated as a result of fasting for one day prior to the operation. Their findings showed inhibition of the renin-angiotensin-aldosterone system and less fluid retention in the third space due to a strong diuretic action.…”
Section: Discussionmentioning
confidence: 99%
“…13) In addition, it has been reported that ANP decreases the demand for furosemide, inhibits potassium loss, reduces electrolyte imbalance, and prevents arrhythmia development during unstable conditions after surgery. [14][15][16][17][18] Thus, it has become a useful drug for perioperative and postoperative management of patients treated in our department. However, the effect on the pulmonary circulation during cardiac surgery has not been examined.…”
Section: Effects Of Continuous Infusion Of Low-dose Human Atrial Natrmentioning
confidence: 99%
“…12 In addition to conventional cardioplegia, we also discussed the method of simultaneous bolus injection of hANP (the "hANP shot") at the time of induction of cardioplegia based on a new concept for increasing cardioprotective effects, and verified the potent myocardial protective effects in animal experiments. 15, 16 The present research is a pilot study to prove the efficacy of the "hANP shot" in clinical cases ("hANP shot" clinical trial).…”
Section: Editorial P 2052mentioning
confidence: 99%
“…Because we found that the 100-μg dose showed stronger cardioprotective effects and did not have adverse effects on the hemodynamics, a dose of 100 μg was used in this study. 15, 16 It was conducted after obtaining approval from the Ethics Committee of Nihon University School of Medicine Itabashi Hospital. Informed consent was provided by each patient after they received an explanation about the study.…”
Section: Study Protocolmentioning
confidence: 99%